2015
DOI: 10.1016/j.joen.2014.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Angiogenesis in Endodontics: Contributions of Stem Cells and Proangiogenic and Antiangiogenic Factors to Dental Pulp Regeneration

Abstract: Introduction Dental pulp regeneration is a part of regenerative endodontics, which includes isolation, propagation, and re-transplantation of stem cells inside the prepared root canal space. The formation of new blood vessels through angiogenesis is mandatory to increase the survival rate of re-transplanted tissues. Angiogenesis is defined as the formation of new blood vessels from preexisting capillaries, which has great importance in pulp regeneration and homeostasis. Here the contribution of human dental pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 99 publications
(116 reference statements)
0
90
0
Order By: Relevance
“…This issue was also raised by Tziafas et al 27) besides the traditional criteria such as easy handling, infection control, good sealing ability, and exploiting endogenous signaling for dentinal bridge formation. These authors also mentioned the use of exogenous signaling molecules in new pulp capping strategies 9) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This issue was also raised by Tziafas et al 27) besides the traditional criteria such as easy handling, infection control, good sealing ability, and exploiting endogenous signaling for dentinal bridge formation. These authors also mentioned the use of exogenous signaling molecules in new pulp capping strategies 9) .…”
Section: Discussionmentioning
confidence: 99%
“…The challenge, however, is to create pulp tissue in a vacant canal, which is exactly identical to the pulpal tissue before necrosis and can function properly 8,9) . This issue is one of the main differences between regenerative attempts and the conventional treatments including apexification.…”
Section: The Effect Of Dental Treatments and Materials On Angiogenesimentioning
confidence: 99%
See 2 more Smart Citations
“…The endothelial shift of MSCs in these studies is mainly indicated by the upregulation of typical endothelial cell (EC) markers, such as PECAM-1, VEGFR-2, vWF, and VE-cadherin and further evidenced by functional assays, such as ability to form capillary-like structures on Matrigel or other matrices or by uptake of Acetylated-Low Density LipoProtein Lipase (Ac-LPL), but also by various in vivo assays, including mouse Matrigel assays and Chicken Chorioallantoic Membrane (CAM) assays [33, 34, 122]. …”
Section: Differentiation Potential and Paracrine Activity Of Dentamentioning
confidence: 99%